The application of artificial technology in pediatric pyeloplasty the efficacy analysis of robotic-assisted laparoscopic pyeloplasty in the treatment of ureteropelvic junction obstruction - Hu, Zhongli; Chen, Shan; Wang, Zhihong; Xu, Di; Zhang, Xiaolang; Lin, Yang; Zhang, Lin; Wang, Jianbin; Li, Lizhi (Frontiers in Pediatrics, 2023)
Objective To investigate the clinical effect of da Vinci robotic-assisted laparoscopic pyeloureteroplasty (RALP) in treating pediatric ureteropelvic junction obstruction (UPJO).We retrospectively analyzed clinical data from thirty-two children with UPJO who suffered from RALP in our hospital from October 2020 to February 2023, compared with those treated with common laparoscopy at the same time. After the 2 establishment of the robotic arm, a mesenteric approach was performed after entering the abdominal cavity to focus on the lesion site. Then dilated renal pelvis was cut and the stenotic ureter was removed, the anastomosis and the incision was sutured by layer.Results Sixty-two children (44 males and 20 females) with a median age of 14 (ranged from 3 to 38) month were included. All 62 cases had hydronephrosis caused by unilateral UPJO, and the surgery were successfully completed without conversion to open. All the intraoperative blood loss was less than 10 ml. In RALP group, the average operative duration was 131.28 (ranged from 108 to 180) min. The average catheter time was 3.66 (ranged from 2 to 7 ) d. The average hematuria time was 3.84 (ranged from 2 to 6 ) d. The average postoperative hospital stay was 7.8 (ranged from 6 to 12) d. The average hospitalization costs was 59048.31 (ranged from 50484 to 69977) yuan. The double-J tube was removed one month after surgery. Only one patient suffered from complications, developing with urinary tract infection four weeks after surgery and was cured after oral cefaclor anti-inflammatory for 3 days.All patients were followed up for 2 to 28 months, with a median follow-up time of 12 months, and the thickness of the renal cortex was increased after surgery [(1.95±0.24) vs. (4.82 ± 0.50)]cm, and the isotope renograms revealed a definite recovery of the split renal function [(28.32±1.95) vs. (37.01±2.71)]%.The robotic-assisted laparoscopic pyeloureteroplasty (RALP) in the treatment of children with upper ureteral obstruction has a overall clinical efficiency. With technological advancements and an increased number of experienced surgeons, 3 robotic surgery may become a new trend in surgery.